(untitled) (Journal of Applied Oral Science, 2008)
The aim of this study was to compare the mechanical strength of different joints made by conventional brazing, TIG and laser welding with and without filling material. Five standardized joining configurations of orthodontic wire in spring hard quality were used: round, cross, 3 mm length, 9 mm length and 7 mm to orthodontic band. The joints were made by five different methods: brazing, tungsten inert gas (TIG) and laser welding with and without filling material. For the original orthodontic wire and for each kind of joint configuration or connecting method 10 specimens were carefully produced, totalizing 240. The fracture strengths were measured with a universal testing machine (Zwick 005). Data were analyzed by ANOVA (p=0.05) and Bonferroni post hoc test (p=0.05). In all cases, brazing joints were ruptured on a low level of fracture strength (186-407 N). Significant differences between brazing and TIG or laser welding (p